Strengthening community actions to improve diabetes mellitus care optimising public health facilitators - Okuhle Nxedlana; Mbuyiselo Douglas; Emmanuel Manu (BMC Health Services Research)
Abstract Background Diabetes mellitus is the second leading cause of death in South Africa, and almost 90,000 people died from diabetes-related causes in the year 2019. This study aimed to investigate facilitators that can be harnessed to strengthen community actions and barriers that should be redressed in structured public health and health promotion programs for people with diabetes mellitus at a primary healthcare level. Methods An exploratory qualitative study was conducted using face-to-face interviews among 20 conveniently sampled participants. The Ottawa Charter was adopted to guide health promotion and strengthening actions for people with diabetes mellitus. This study was conducted at Ngangelizwe Community Health Centre. Ngangelizwe is one of the townships located about 2 km east of Mthatha Town in the Eastern Cape Province of South Africa. The thematic analysis method was used to analyse data with the assistance of Atlas ti, version 23 software. Results Five overarching themes were yielded and categorized as facilitators and barriers. Facilitators included enhancing the role of community healthcare workers and strengthening health education activities. Barriers included lack of support groups, food insecurity, and unavailability of community health promotion programs. Conclusion We conclude that a collaborative health promotion intervention with the necessary competencies should be designed to assess needs and develop, implement, and evaluate relevant empowerment programs at the household and community levels. This approach involves active engagement with health promoters/ public health practitioners and community health workers at the local level, allowing individuals and communities to access motivation and knowledge regarding the control of diabetes mellitus.